Drivability of Large Diameter Steel Cylinders During Hammer-Group Vibratory Installation for the Hong Kong–Zhuhai–Macao Bridge. (January 2023) - Lu, W.J.; Li, B.; Hou, J.F.; Xu, X.W.; Zou, H.F.; Zhang, L.M.
Abstract: The Hong Kong–Zhuhai–Macao Bridge (HZMB) involved the installation of 120 mega-cylinders with a diameter of 22 m, weights up to 513 t, and penetration depths up to 33 m using an eight-vibratory hammer group. Due to the lack of engineering experience on the drivability of large-diameter cylinders under multiple vibratory hammers, predicting the penetration rate and time of steel cylinders is an open challenge that has a considerable impact on the construction control of the HZMB. In this study, the vibratory penetration of large-diameter steel cylinders in the HZMB is investigated based on geological surveys, field monitoring, and drivability analysis. The vibratory penetration rate, installation accuracy, and dynamic responses of the steel cylinders at both the eastern and western artificial islands are analyzed. The dynamic soil resistance has a great influence on the cylinder drivability. However, the current design methods for estimating the vibratory driving soil resistance are proven inaccurate without considering the scale effects. Therefore, a modified method with a normalized effective area ratio A ¯ r, eff is proposed in this study to calculate the vibratory soil resistance for open-ended thin-wall cylinders under unplugged conditions. Considering the scale effects on the vibratory driving soil resistance, the proposed method leads to closer results to the measured data, providing a reference for future engineering practice.